Communication in knowledge management practices: A survey from turkey - (:unkn) unknown (LLC CPC Business Perspectives, 2009)
The diffusion and usage of ICT have caused new applications related to knowledge activities in organizations in last decades. Knowledge management (KM), one of them, has been developed based on both computer-based technologies and management level concerns such as management information systems, intellectual capital, etc. This study aims to define importance of communication and to reveal communication tools in KM processes. In data collection phase, the inquiry was sent to 9 companies and 103 managers/employees from different levels retrieved. Findings show that communication is important dimension of knowledge management as well as technology, leadership, culture and it is mostly used for explicit knowledge sharing. © Özhan Tingoy, Özlem Efiloǧlu Kurt, 2009.
Keywords: Communication; Knowledge management; Turkey